Effect-based water quality assessment of rivers receiving discharges from legacy mines by using acute and chronic bioassays with two cladoceran species. Issue 4 (3rd January 2022) - Mano, H.; Iwasaki, Y.; Shinohara, N.
Abstract: Information about the ecotoxicological impacts of surface waters that receive discharges from legacy mines is valuable to infer the ecological impacts on natural environment for managing mine discharges. In this study, we investigated behavioural and reproductive responses of two cladoceran species Ceriodaphnia dubia and Daphnia magna to water samples collected from metal-contaminated and reference rivers near legacy mines in Japan. The toxicity identification evaluation (TIE) of water samples that caused D. magna immobility was conducted to evaluate the key metals causing acute toxicity. The results of our water quality assessment performed using two cladoceran species demonstrated modest to significant adverse effects on their behaviour and reproduction, suggesting the potential for ecotoxicological impacts on natural populations and communities at several contaminated sites that received mine drainage. The results of TIE of water samples that caused D. magna immobility indicated likely contributions of Zn and Cu. These results imply that effect-based water quality assessments such as ours can provide direct and unique evidence of the ecotoxicological impacts of metals in river waters, which will be useful for better understanding and predicting the ecological effects of these metals in the natural environment. HIGHLIGHTS: Results of effect-based water quality assessment by using two cladoceran species suggest the potential ecotoxicological impacts at contaminated rivers receiving mine drainages in Japan. Toxicity identification evaluation of water samples suggested a major contribution of Zn and Cu. Effect-based water quality assessments can provide direct and unique evidence of the ecotoxicological impacts of metals.